2016
DOI: 10.3390/nano6110198
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Emission Energy of Chemically Doped Graphene Quantum Dots

Abstract: Tuning the emission energy of graphene quantum dots (GQDs) and understanding the reason of tunability is essential for the GOD function in optoelectronic devices. Besides material-based challenges, the way to realize chemical doping and band gap tuning also pose a serious challenge. In this study, we tuned the emission energy of GQDs by substitutional doping using chlorine, nitrogen, boron, sodium, and potassium dopants in solution form. Photoluminescence data obtained from (Cl- and N-doped) GQDs and (B-, Na-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 38 publications
(58 reference statements)
1
14
0
Order By: Relevance
“…The PL shift was even higher in the carbon dots from activated precursors (Cd.CB < Cd.H 2 SO 4 < Cd.H 2 SO 4 + KOH < Cd.KOH). A hypsochromic or bathochromic shift is caused by a bandgap modification [ 73 , 74 , 75 , 76 ]. A hypsochromic PL shift is observed with a widening of the bandgap, while the opposite (a bathochromic shift) occurs by narrowing the bandgap [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PL shift was even higher in the carbon dots from activated precursors (Cd.CB < Cd.H 2 SO 4 < Cd.H 2 SO 4 + KOH < Cd.KOH). A hypsochromic or bathochromic shift is caused by a bandgap modification [ 73 , 74 , 75 , 76 ]. A hypsochromic PL shift is observed with a widening of the bandgap, while the opposite (a bathochromic shift) occurs by narrowing the bandgap [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…A hypsochromic or bathochromic shift is caused by a bandgap modification [ 73 , 74 , 75 , 76 ]. A hypsochromic PL shift is observed with a widening of the bandgap, while the opposite (a bathochromic shift) occurs by narrowing the bandgap [ 73 ]. This bandgap is highly dependent on the nanoparticle size and the surface functionalization.…”
Section: Resultsmentioning
confidence: 99%
“…Several synthesis methods were reported recently. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Minati et al [22][23] investigated the photoluminescence spectra of short oxidized multi walled carbon nanotubes which are luminescent in the visible range. Minati et al 24 and his group in 2010 reported a new method for the high yield isolation of strongly photoluminescent GQD from oxidized carbon nanotubes (ox-CNT).…”
mentioning
confidence: 99%
“…Qu et al 20 have demonstrated that S, N-GQDs processed much better absorption of visible light than pure GQDs and multicolor emission under visible light excitation. Ain et al 29 observed the red and blueshift, obtained from PL, by substitutional doping while using different dopants [Cl, N, Na, K, B] to tune the emission energy of GQDs. Zhou et al 30 prepared a simple and efficient method of the photo-Fenton reaction after breaking C-C bond of GO to produce GQDs in large scale.…”
mentioning
confidence: 99%
“…Once the reagent of BD continues to increase, the enlarged particle size of CQDs reduced the distance between CQDs (as shown in Figure 2 ), so that the π–π interaction can be effectively occurred, which finally resulted in hypochromic effect [ 82 , 83 ]. Moreover, Noor-Ul-Ain reported doping chlorine into CQDs would introduce additional energy level between the C π -C π *, called the Cl-related states [ 84 ]. The corresponding absorption peak at 292 nm observed in our samples coincided with the calculated transition energy from C π to Cl-related states [ 28 , 69 ].…”
Section: Resultsmentioning
confidence: 99%